2010
DOI: 10.1177/1352458510373487
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic impact of a specialty care management program among patients with multiple sclerosis: a cohort study

Abstract: Background: To evaluate the clinical and economic impact of a specialty care management program among patients with multiple sclerosis.Methods: This retrospective cohort analysis included patients aged ≥18 years with ≥2 claims of multiple sclerosis diagnosis and ≥1 multiple sclerosis medications from 1 January 2004 to 30 April 2008. The outcome metrics included medication adherence and persistence, multiple scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 23 publications
(27 reference statements)
4
70
0
1
Order By: Relevance
“…15 Nonadherence to DMTs has been shown to have a negative impact on clinical outcomes, including higher rates of relapse and disease progression, 16,17 as well as an increase in hospital resource utilization. 18 However, according the the European Multiple Sclerosis Therapy Consensus Group (MSTCG) guidelines, patients may discontinue treatment with DMTs after 3 years, if there is no evidence of relapse and/or progression. 19 This review focuses on patient adherence to therapy, a distinct concept from persistence to therapy.…”
Section: Drug and Date Of Fda Approvalmentioning
confidence: 99%
“…15 Nonadherence to DMTs has been shown to have a negative impact on clinical outcomes, including higher rates of relapse and disease progression, 16,17 as well as an increase in hospital resource utilization. 18 However, according the the European Multiple Sclerosis Therapy Consensus Group (MSTCG) guidelines, patients may discontinue treatment with DMTs after 3 years, if there is no evidence of relapse and/or progression. 19 This review focuses on patient adherence to therapy, a distinct concept from persistence to therapy.…”
Section: Drug and Date Of Fda Approvalmentioning
confidence: 99%
“…43 Problems with injections, perceived lack of efficacy, and side effects have been identified as major barriers to long-term adherence in patients with MS. 54 MCOs have an interest in clinical programs that can reduce the higher medical expenditures incurred by MS patients. 52 A condition management program for MS described by Tan et al (2010) was associated with improved medication adherence and persistence, reduced MS-related hospitalizations, and decreased MS-related medical costs. 55 However, the authors concluded that the cost savings in the medical component (-$264) during the 12-month follow-up period did not offset the increased pharmacy expenditures for MS drugs (+$2,184).…”
Section: Ms Medication Safety and Remsmentioning
confidence: 99%
“…52 A condition management program for MS described by Tan et al (2010) was associated with improved medication adherence and persistence, reduced MS-related hospitalizations, and decreased MS-related medical costs. 55 However, the authors concluded that the cost savings in the medical component (-$264) during the 12-month follow-up period did not offset the increased pharmacy expenditures for MS drugs (+$2,184). Interventions included direct mailing of medication and disease-specific patient education materials to patients, including refill reminder calls.…”
Section: Ms Medication Safety and Remsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, specialty drug care management programs have shown positive outcomes in the quality of care for disease states such as hemophilia, 8 MS, [9][10][11] HIV, 12 and other diseases. Specialty management strategies include custom formularies and benefit designs, clinical utilization management, provider reimbursement contracts, fraud and billing error monitoring, and distribution channel management.…”
Section: Opportunities and Challenges Of Specialty Pharmaceuticalsmentioning
confidence: 99%